2014
DOI: 10.5958/j.0976-058x.48.3.029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of canopy temperature and stress degree day index on dry matter accumulation and grain yield of wheat (Triticum aestivumL.) sown at different dates in the Indo-Gangetic plains of Eastern India

Abstract: Temperature change with concomitant change in canopy temperature influences crop growth and productivity. A three year (2005-06 to 2007-08) experiment was carried on wheat varieties PBW 343, HD 2733, HW 2045, PB 533 and K9107 in subplot treatments sown on three dates of 18 th November, 3 rd and 18 th December in main-plot treatments in a split-plot design with three replications. Canopy temperature was measured at CRI, tillering, flowering and milking and stress degree day index was computed. Late sown crop ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…Variations in atmospheric temperature have become a major concern with respect to agricultural production. Plants being poikilothermic in nature, any change in temperature summons change in canopy temperature, inevitably affecting their growth and productivity (Basu et al, 2014). Measurement of canopy temperature is necessary to understand the plant-water status at a particular phenophase of a crop.…”
mentioning
confidence: 99%
“…Variations in atmospheric temperature have become a major concern with respect to agricultural production. Plants being poikilothermic in nature, any change in temperature summons change in canopy temperature, inevitably affecting their growth and productivity (Basu et al, 2014). Measurement of canopy temperature is necessary to understand the plant-water status at a particular phenophase of a crop.…”
mentioning
confidence: 99%
“…Babiker et al (2017) also revealed that the effect of location was highly significant for both falling number and rate of germination, and was significant for germination percentage. Basu et al (2014) have added that optimum temperature that supports the growth of wheat plants is under 24 0 C. Therefore, wheat crops which are needed are those which are able to adapt in the middle plains (400-800 m.a.s.l.). Therefore, the farmers said that wheat farming should be carried out on highlands.…”
Section: Farmers' Perceptions Towards Wheat Farmingmentioning
confidence: 99%
“…Kata kunci: filogenetik, genotipe introduksi, kekerabatan, keragaman, suhu tinggi tidak dapat dibudidayakan pada dataran rendah di Indonesia karena tingginya suhu. Basu et al (2014) menambahkan suhu optimum yang mendukung pertumbuhan tanaman ini adalah <24 o C. Oleh karena itu, diperlukan tanaman gandum yang mampu beradaptasi di dataran menengah (400-800 m dpl).…”
Section: Abstrakunclassified